Science and Scepticism in the Early Mission to New France - Goddard, Peter (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1995)
AbstractFar from being naive and credulous observers, the first Jesuit missionaries to New France (1611-1650) were sceptical and rationalistic in their analyses of nature and natural forms of life. Despite the rhetoric of spiritual conquest found in the Jesuit Relations, and a theological focus on the sinfulness of all nature including the human, missionary curiosity extended beyond the narrowly religious. As a group, Jesuit missionaries were remarkably empirically minded when investigating native spirituality and when testing claims about the supernatural. They thus demonstrate affinity with the emerging culture of scientific reason in early modern Europe.